Ozempic and its Protective Factors in Relation to Acute Myocardial Infarction (Global Journal of Medical Research, 2023)
Introduction The World Health Organization WHO estimates that cardiovascular diseases account for 31 of all deaths each year making them the leading cause of death worldwide As such the search to reduce rates through the development of new treatments and approaches is incessant Methodology This is a literature review whose bases were taken from the SciELO and PubMed data platforms The search period was July 2023 meeting the inclusion criteria of articles from 2000 to 2023 in Portuguese and English online and in full text Discussion Cardiovascular diseases CVD are the leading cause of death worldwide and are among the main causes of disability and years of life lost having an important social economic and quality of life impact on the population 1 2 Cardiovascular risk factors include high cholesterol levels diabetes mellitus a sedentary lifestyle high blood pressure and obesity